Understanding Hellenistic Thanatos: death, ritual and identity in the south-eastern Aegean in the late 4th-1st c. BC - Brouma, Vasiliki (2017)
The aim of this thesis is to examine ritual action and identity formation in the funerary record of the South-Eastern Aegean during the Hellenistic period (late 4th – 1st centuries BC).